Characteristics of the Karakalpak Strain of B.Bifidum Kk, Promising for Use as a Probiotic - Narymbetova, Rosa (Asian Pacific Journal of Environment and Cancer, 2021)
The article presents the results of a study on the physiological, biochemical and technological properties of the local (karakalpak) strain of Bifidobacterium bifidum KK. Antagonistic activity of the strain in relation to Escherichia coli, Staphylococcus aureus, Proteus vulgaris, relation to intestinal metabolism products and sensitivity to drugs was studied. It has been established that the karakalpak strain of Bifidobacterium bifidum KK has high technological properties and can be recommended as a probiotic to supplement the actual nutrition of children and adults.